2009
DOI: 10.1007/s10265-009-0274-0
|View full text |Cite
|
Sign up to set email alerts
|

Carbon cycling and net ecosystem production at an early stage of secondary succession in an abandoned coppice forest

Abstract: Secondary mixed forests are one of the dominant forest cover types in human-dominated temperate regions. However, our understanding of how secondary succession affects carbon cycling and carbon sequestration in these ecosystems is limited. We studied carbon cycling and net ecosystem production (NEP) over 4 years (2004-2008) in a cool-temperate deciduous forest at an early stage of secondary succession (18 years after clear-cutting). Net primary production of the 18-year-old forest in this study was 5.2 tC ha(-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 34 publications
(44 reference statements)
3
21
0
Order By: Relevance
“…Temporal change in R s is primarily controlled by T s in many temperate deciduous forests [6][7][8]; R s generally increases with an exponential increase in T s within the range 0-25 • C. In concurrence with these previous investigations, the present study showed a pattern of increasing R s with increasing T s (Figure 7).…”
Section: Effect Of Soil Temperature and Soil Water Content On Soil Resupporting
confidence: 91%
See 2 more Smart Citations
“…Temporal change in R s is primarily controlled by T s in many temperate deciduous forests [6][7][8]; R s generally increases with an exponential increase in T s within the range 0-25 • C. In concurrence with these previous investigations, the present study showed a pattern of increasing R s with increasing T s (Figure 7).…”
Section: Effect Of Soil Temperature and Soil Water Content On Soil Resupporting
confidence: 91%
“…For evaluation of annual R s using equations, seasonal R s has often been estimated using only T s dependence as an exponential relationship in forests where W is not limiting (e.g., [6][7][8][43][44][45]). However, in forests where there is a drying period, R s has been estimated by the coupling of T s and W, although an empirical model using these variables has been unclear [3,31,[35][36][37][38][39].…”
Section: Estimation Of Soil Respiration In the Old-growth Forestmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, there was a tree in this community damaged by wild animals in 2012 but it was recovering very fast. The uptake of organic carbon in this community seems to be higher than other communities as Ohtsuka et al (2010) states that the damage recovery is faster in younger forests which affects the production.…”
Section: Soil Organic Carbonmentioning
confidence: 78%
“…The reason why standing biomass, annual net production, and plant organic carbon show different values to other research is because forest age and tree density of different research sites have influenced the study. Kimmins (1987) stated that the standing biomass and net production increases with aging of the forest in case of young forests given that community structure of the forest is similar and Ohtsuka et al (2010) also reported that the increase of biomass and net production of younger forest is greater than the older forest. In addition, the NPP of forest ecosystem typically changes with the forest age, and it starts to decrease once dense pioneer community reaches its peak (Marks 1974, Smith and Long 2001, Binkley et al 2002.…”
Section: Organic Carbon Of Litter Productionmentioning
confidence: 99%